Strengthening Hospitals for a Post-COVID-19 Future in Poland - World Bank (World Bank, Washington, DC, 2021)
The outbreak of the coronavirus disease Coronavirus (COVID-19) pandemic has delivered an enormous shock to the global economy, exacting a large human toll, shutting down major economic sectors, and deeply upending labor markets. The objective of this analysis is to identify pragmatic steps to improve hospital performance in Poland and propose actionable short- and medium-term roadmaps for reforming hospitals post Coronavirus (COVID-19). The World Bank health team has a long history of engagement in the health sector in Poland and has built on various pieces of analysis to meet the objectives of this study. In addition to studying the hospital sector and the reform experience to date, the study team has held focused discussions with senior executives at Polish hospitals and other key stakeholders within the Polish health care system. Drawing upon expertise in hospital evaluation and management, health economics, and health services research, the study team identifies and assesses the critical challenges facing Polish hospitals in the areas of efficiency and effectiveness and proposes recommendations that key stakeholders can launch in the short or medium term to begin to address those challenges. While the Coronavirus (COVID-19) pandemic has had an enormous impact on the Polish hospital system over the last fourteen months, this analysis focuses on the anticipated post-pandemic environment for hospitals.